Reformation commentary on scripture 1 New Testament 1 Matthew / edited by Jason K. Lee and William M. Marsh ; general editor, Timothy George ; associate general editor, Scott M. Manetsch - Lee, Jason K.; Marsh, William M.; George, Timothy 1950-; Manetsch, Scott M. 1959- (Downers Grove, IL IVP Academic, 2021)
Introduction to Matthew -- Commentary on Matthew -- Map of Europe at the time of the Reformation -- Timeline of the Reformation -- Biographical sketches of Reformation-era figures and works.
"The sixteenth-century Reformers turned to Scripture to find the truth of God's Word, but that doesn't mean they always agreed on how to interpret it. This RCS volume guides readers through a wealth of early modern commentary on the book of Matthew, drawing upon a variety of resources and voices from a diversity of theological traditions"--
Includes bibliographical references and indexes
Keywords: Bible -- Commentaries; Theology -- History -- 16th century; Reformation; Kommentar